2010
DOI: 10.1038/aps.2010.110
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline alleviates high-fat diet-induced non-alcoholic steatohepatitis and early atherosclerosis in rats by inhibiting AGE and RAGE expression

Abstract: Aim:To investigate the expression of advanced glycation end products (AGEs) and their receptor RAGE in the livers and blood vessels of rats with non-alcoholic steatohepatitis (NASH) and the effect of pentoxifylline (PTX) on liver and artery function in rats with NASH. Methods: Sprague-Dawley rats were fed a high-fat diet for 12 weeks and given PTX by gavage for 4 weeks. The effects of PTX on hepatic liver and vessel function as well as the expression of AGE and RAGE in rats with NASH were assessed. The intima-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Advanced glycation end products (AGEs) and their receptor (RAGE) have also been suggested to contribute to the pathogenesis of NASH in HFD-fed rats [18,19]. Also, oxidative stress has been reported to increase glycated protein levels [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced glycation end products (AGEs) and their receptor (RAGE) have also been suggested to contribute to the pathogenesis of NASH in HFD-fed rats [18,19]. Also, oxidative stress has been reported to increase glycated protein levels [20].…”
Section: Resultsmentioning
confidence: 99%
“…Protein glycation and its markers namely AGEs and their receptor RAGE, were reported to increase in rat fed HFD, contributing NASH pathogenesis [18,19]. Based on this information and the fact that liver is the main organ to clear AGEs, it was logical to evaluate protein glycation/glycosylation in the present model.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with a previous study, where Sprague-Dawley rats fed a HFD for 16 wk were treated with pentoxifylline for 4 wk (16 mg/kg per day). The results showed decreased AST levels but not ALT, and improvements in basal glucose but not HOMAIR index [19] . Additionally, in a previous study of Sprague-Dawley fed HFD for 10 wk and treated with pentoxifylline for 6 wk (50 mg/kg per day), hepatic steatosis and plasma levels of TNF-α were reduced [20] .…”
Section: Metabolic and Anthropometric Parameters After Pentoxifyllinementioning
confidence: 89%
“…Oxidative/nitrative stress has been reported to cause various post-translational modifications of Cys-residues of cellular proteins [23], [29], [32], which negatively affect physiological functions of some essential proteins, prior to the observation of full-blown liver disease [29]. In addition, AZT-treated mice showed significantly higher levels of hepatic AGEs, which can potently trigger ROS production, as demonstrated in experimental models of NASH [21], [43], [44], as compared to the vehicle-treated control, further confirming higher oxidative stress in AZT-treated animals. Further, Gao et al [45] have shown that production of ROS in AZT-exposed primary cardiomyocytes could be attenuated by using resveratrol, a plant-derived anti-oxidant.…”
Section: Discussionmentioning
confidence: 99%